Development of Postural Control in Healthy Children: A Functional Approach. Issue 2 (2005) - Assaiante, Christine; Mallau, Sophie; Viel, Sébastien; Jover, Marianne; Schmitz, Christina
Abstract : From a set of experimental studies showing how intersegmental coordination develops during childhood in various posturokinetic tasks, we have established a repertoire of equilibrium strategies in the course of ontogenesis. The experimental data demonstrate that the first reference frame used for the organization of balance control during locomotion is the pelvis, especially in young children. Head stabilization during posturokinetic activities, particularly locomotion, constitutes a complex motor skill requiring a long time to develop during childhood. When studying the emergence of postural strategies, it is essential to distinguish between results that can be explained by biomechanical reasons strictly and those reflecting the maturation of the central nervous system (CNS). To address this problem, we have studied our young subjects in situations requiring various types of adaptation. The studies dealing with adaptation of postural strategies aimed at testing short and long-term adaptation capacity of the CNS during imposed transient external biomechanical constraints in healthy children, and during chronic internal constraints in children with skeletal pathologies. In addition to maintenance of balance, another function of posture is to ensure the orientation of a body segment. It appears that the control of orientation and the control of balance both require the trunk as an initial reference frame involving a development from egocentric to exocentric postural control. It is concluded that the first step for children consists in building a repertoire of postural strategies, and the second step consists in learning to select the most appropriate postural strategy, depending on the ability to anticipate the consequence of the movement in order to maintain balance control and the efficiency of the task.